Structural basis for the interaction of the fluorescence probe 8-anilino-1-naphthalene sulfonate (ANS) with the antibiotic target MurA - Schönbrunn, Ernst (National Academy of Sciences, 2000)
The extrinsic fluorescence dye 8-anilino-1-naphthalene sulfonate (ANS) is widely used for probing conformational changes in proteins, yet no detailed structure of ANS bound to any protein has been reported so far. ANS has been successfully used to monitor the induced-fit mechanism of MurA [UDPGlcNAc enolpyruvyltransferase (EC 2.5.1.7)], an essential enzyme for bacterial cell wall biosynthesis. We have solved the crystal structure of the ANS⋅MurA complex at 1.7-Å resolution. ANS binds at an originally solvent-exposed region near Pro-112 and induces a major restructuring of the loop Pro-112–Pro-121, such that a specific binding site emerges. The fluorescence probe is sandwiched between the strictly conserved residues Arg-91, Pro-112, and Gly-113. Substrate binding to MurA is accompanied by large movements especially of the loop and Arg-91, which explains why ANS is an excellent sensor of conformational changes during catalysis of this pharmaceutically important enzyme.